1997
DOI: 10.1080/13664539700200010
|View full text |Cite
|
Sign up to set email alerts
|

Developing as mentors in school-based teacher training

Abstract: This article presents interim findings from a 2-year comparative study of two models of Postgraduate Certificate in Education (PGCE) secondary Initial Teacher Education (ITE). These models are represented by a newly established school-administered programme (SAP) and a higher education-administered programme (HEAP). The nature of the mentoring role and some of the factors which are influential on mentoring-specific professional development are considered. In particular, the paper focuses on two factors; suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 5 publications
0
19
0
2
Order By: Relevance
“…Rather than inviting them to think about why events occurred, confronting their actions, and encouraging the students themselves to consider how they might 'reconstruct' their teaching approaches (Smyth,1989), school-based mentors tended to tell students what their areas of weakness were, how to handle a particular situation and which teaching strategies to use. The practical nature of mentors' guidance has been noted in other research studies (Ashby et al 2008, Hobson 2002, Evans & Abbott, 1997 and may be as a result of lack of training or simply pressure of time.…”
Section: Mentor Feedbackmentioning
confidence: 96%
“…Rather than inviting them to think about why events occurred, confronting their actions, and encouraging the students themselves to consider how they might 'reconstruct' their teaching approaches (Smyth,1989), school-based mentors tended to tell students what their areas of weakness were, how to handle a particular situation and which teaching strategies to use. The practical nature of mentors' guidance has been noted in other research studies (Ashby et al 2008, Hobson 2002, Evans & Abbott, 1997 and may be as a result of lack of training or simply pressure of time.…”
Section: Mentor Feedbackmentioning
confidence: 96%
“…Bullough, 2005). Some studies have also reported that mentoring is more likely to direct to constructive outcomes where mentors obtain reward and/or some other form of enticement or acknowledgement for their work (Abell et al,1995;Evans & Abbott, 1997;Simpson et al,2007); where it takes place in environments which are comparatively free from extreme emphases on externally resolute aims and agendas such as narrow criteria for teaching practices (Edwards, 1998;Gay & Stephenson, 1998;Yusko & Feiman Nemser, 2008); where mentors are involved in the plan and assessment of and are devoted to, the broader (ITP, orientation or early professional development) programs of which mentoring is a part (Evans & Abbott, 1997); and where such programs are coherent and not characterized by 'fragmentation' (Goodlad, 1990) between various (e.g. school-based and university-based) contributors (Hascher, et al, 2008).…”
Section: Contextual Support For Mentoringmentioning
confidence: 99%
“…Comme les difficultés que rencontrent certains enseignants chevronnés dans leurs fonctions de mentor sont susceptibles d'entraver la réussite du dispositif de mentorat, il est important que les mentors reçoivent de la formation et du soutien professionnel afin de développer leurs compétences et de surmonter les obstacles rencontrés (Duchesne et Kane, 2010;Gagnon, 2017 ;Kane, Jones, Rottmann et Conner, 2010). En effet, des études ont mis en évidence l'importance d'orienter les mentors vers des ressources nécessaires et appropriées pouvant les outiller davantage sur le plan de leurs pratiques mentorales (Evans et Abbott, 1997) ou de les aider à comprendre la portée et les bénéfices potentiels de leurs discussions avec les mentorés à propos de divers enjeux pédagogiques (Lindgren, 2005). Rippon et Martin (2006), pour leur part, rappellent l'importance de prodiguer aux mentors une formation axée sur le développement des compétences interpersonnelles nécessaires à l'établissement d'une relation mentorale fertile.…”
Section: La Préparation La Formation Et Le Soutien Des Mentorsunclassified
“…Des études ont mis en évidence l'importance d'outiller davantage les mentors sur le plan de leurs pratiques d'accompagnement (Evans et Abbott, 1997, Gagnon, 2017. Or, les quatre mentors rencontrés affirment n'avoir reçu que très peu d'information, de soutien ou d'encadrement de la part des membres de la direction d'école ou du conseil scolaire.…”
Section: La Préparation La Formation Et Le Soutien Des Mentorsunclassified